2021
DOI: 10.1016/j.jiph.2021.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of SARS-CoV-2 infection following recovery from COVID-19

Abstract: Introduction Many individuals test positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA after recovering from the coronavirus disease (COVID-19), but the incidence of reactivation is unknown. We, therefore, estimated the incidence of reactivation among individuals who had recovered from COVID-19 and determined its predictors. Methods In this retrospective cohort study, patients with COVID-19 were followed up for at least 14 days after two consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Numerous studies have reported that one or more symptoms of COVID‐19 persist for more than a month after recovery. 1 , 4 , 5 , 6 Fatigue and dyspnea have been reported as the most common persistent complaints after recovery from COVID‐19. 4 , 7 Several studies have indicated that the persistence of symptoms is not linked to a certain age, gender, or severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported that one or more symptoms of COVID‐19 persist for more than a month after recovery. 1 , 4 , 5 , 6 Fatigue and dyspnea have been reported as the most common persistent complaints after recovery from COVID‐19. 4 , 7 Several studies have indicated that the persistence of symptoms is not linked to a certain age, gender, or severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Re‐infection with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has been reported in several studies. 5 , 6 The severity of the second attack varies over all the studies. Prado‐Vivar et al 5 reported that the second infection is more severe than the first one while Chen et al 6 documented that 75% of patients with re‐infection were asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…The literature search revealed a total of 4833 related articles. After removal of duplicates and application of the inclusion and exclusion criteria, 22 articles 5 26 remained. The detailed process of study screening is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The findings of new studies clearly support the key idea discussed in our article, “Can Reactivation of SARS-CoV-2 Decrease the Chance of Success of Future Deep Space Missions?” 2 . Regarding reactivation, a recent study 6 showed that among 109 patients, 29 experienced reactivation (27%), and seven of these were symptomatic (24%). Given this consideration, during a long-term space mission, when the immune system starts to weaken, the dormant infection may progress to a severe infection.…”
mentioning
confidence: 99%